A Delphi consultation to assess indicators of readiness to provide quality health facility-based lymphoedema management services. - Victoria L Walsh; LeAnne M Fox; Molly Brady; Jonathan King; Caitlin M Worrell (Public Library of Science (PLoS), 2018)
BACKGROUND:The World Health Organization (WHO) in collaboration with partners is developing a toolkit of resources to guide lymphatic filariasis (LF) morbidity management and disability prevention (MMDP) implementation and evaluation. Direct health facility inspection is the preferred method for documenting the readiness of a country programme to provide quality lymphoedema management services, one of the three MMDP criteria used to demonstrate the elimination of LF as a public health problem. METHODOLOGY/PRINCIPAL FINDINGS:As component of tool development, a Delphi consultation was implemented to gain consensus on six proposed domains and fourteen proposed tracer indicators to measure national programme readiness to provide quality health facility-based lymphoedema management services. A seven-point Likert-type scale was used to rank the importance of proposed domains and tracer indicators. Consensus for inclusion of the indicator was defined a priori as 70% or more of respondents ranking the proposed indicator in the top three tiers (5-7). Purposive sampling was used to select 43 representative experts including country representatives, programme implementers, and technical experts. A 55.8% response rate (n = 24) was achieved for the survey. Analysis of the responses demonstrated that consensus for inclusion had been reached for all proposed domains including trained staff (mean = 6.9, standard deviation (SD) = 0.34), case management and education materials (mean = 6.1, SD = 0.65), water infrastructure (mean = 6.3, SD = 0.81), medicines and commodities (mean = 6.3, SD = 0.69), patient tracking system (mean = 6.3, SD = 0.85), and staff knowledge (mean = 6.5, SD = 0.66). SIGNIFICANCE:The Delphi consultation provided an efficient and structured method for gaining consensus among lymphatic filariasis experts around key lymphoedema management quality indicators. The results from this analysis were used to refine the indicators included within the direct inspection protocol tool to ensure its ability to assess health facility readiness to provide quality lymphoedema management services.